2012
DOI: 10.1007/s11302-012-9334-3
|View full text |Cite
|
Sign up to set email alerts
|

Functional selectivity of adenosine A1 receptor ligands?

Abstract: The concept of functional selectivity offers great potential for the development of drugs that selectively activate a specific intracellular signaling pathway. During the last few years, it has become possible to systematically analyse compound libraries on G protein-coupled receptors (GPCRs) for this 'biased' form of signaling. We screened over 800 compounds targeting the class of adenosine A(1) receptors using a β-arrestin-mediated signaling assay in U2OS cells as a G protein-independent readout for GPCR act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…A 1 AR-biased agonism has been previously investigated (Langemeijer et al, 2013;Valant et al, 2014;Baltos et al, 2016) and recently demonstrated to allow for the selective stimulation of cardioprotective signal transduction in the absence of the adverse hemodynamic effects commonly associated with A 1 AR therapies (Valant et al, 2014). The current study has identified a range of bias profiles for subtype selective A 3 AR agonists, which offer a potential therapeutic advantage.…”
Section: Discussionmentioning
confidence: 83%
“…A 1 AR-biased agonism has been previously investigated (Langemeijer et al, 2013;Valant et al, 2014;Baltos et al, 2016) and recently demonstrated to allow for the selective stimulation of cardioprotective signal transduction in the absence of the adverse hemodynamic effects commonly associated with A 1 AR therapies (Valant et al, 2014). The current study has identified a range of bias profiles for subtype selective A 3 AR agonists, which offer a potential therapeutic advantage.…”
Section: Discussionmentioning
confidence: 83%
“…The functional selectivity of different signalling pathways offers a new opportunity for developing signalling pathway-biased drugs that selectively activate a specific intracellular adenosine receptor signalling pathway that is essential for a particular biological function. By systematically screening compound libraries of GPCRs for this ‘biased’ form of signalling, β-arrestin-biased D 2 receptor ligands were successfully identified 245 and the discovery of a β-arrestin-biased A 1 receptor ligand was also attempted, albeit with limited success 246 . New knowledge of the diversity and modularity of GPCR structures, the A 2A receptor in particular, from a recent structural biology crystallization study offers opportunities to target receptor structures with different signalling functions 239 .…”
Section: Overview Of Adenosine Receptorsmentioning
confidence: 99%
“…Our study presents a variation on these methods, in that we purposefully exploit the allosteric nature of GPCRs to maximize the likelihood that a biased ligand can be rationally engineered from the outset. This approach is especially noteworthy given that previous screening studies have been unable to identify biased ligands at the A 1 AR (47,48). Moreover, assaying of the engineered biased ligand in native A 1 AR-expressing systems revealed unique properties, suggesting a favorable efficacy vs. side effect profile.…”
Section: Discussionmentioning
confidence: 99%